Analysis of a super-transmission of SARS-CoV-2 omicron variant BA.5.2 in the outdoor night market - Luo, Mingyu; Liu, Shelan; Zhu, Liebo; Wang, Fengying; Wu, Kunyang; He, Hanqing; Qi, Xiaohua; Pang, Zhifeng; Dong, Xuanjun; Gong, Zhenyu; Yu, Min (Frontiers in Public Health, 2023)
Introduction The COVID-19 pandemic continues to ravage the world, and mutations of the SARS-CoV-2 continues. The new strain has become more transmissible. The role of aerosol transmission in the pandemic deserves great attention. Methods In this observational study, we collected data from market customers and stallholders who had been exposed to the virus in the Qingkou night market on July 31 and were subsequently infected. We analyzed the possible infection zones of secondary cases and aerosol suspension time in ambient air. We described and analyzed the characteristics of the secondary cases and the transmission routes for customers. Results The point source outbreak of COVID-19 in Qingkou night market contained a cluster of 131 secondary cases. In a less-enclosed place like the Qingkou night market, aerosols with BA.5.2 strain released by patients could suspend in ambient air up to 1 h 39 min and still be contagious. Conclusion Aerosols with viruses can spread over a relatively long distance and stay in ambient air for a long time in a less enclosed space, but shorter than that under experimental conditions. Therefore, the aerosol suspension time must be considered when identifying and tracing close contact in outbreak investigations.